The role of export taxes in the field of primary commodities - Piermartini, Roberta (WTO Pub. GenevaCH, 2004)
Examines the economic effects of an export tax on commodity prices and the volume of exports. Focuses on positive and negative aspects of an export tax as an instrument of trade policy to improve developing countries' terms-of-trade, reduce commodity price fluctuations and inflationary pressures, favour economic diversification, ease government revenue collection and help the poor in a country. Illustrates some of the economic implications of export taxes by sharing selected countries experiences.